Analisis Strategi Perilaku Konsumen Terhadap Cita Rasa Kopi Luwak - Ananda Aprilia; Halimah Zahrah; Yunisa Nuramalia; Dea Ingrid Ramadani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Civet coffe is one of the distinctive types of coffe from Indonesia that is famous for its unique production process and the taste of civet coffe,which raises questions about how consumer perceptions and behaviors toward this product are formed.The main issue in this research is how consumers interpret the taste of civet coffe and what factors influence their product.This study aims to again an in-depth understanding of consumer perceptions of the taste of civet coffe and to explore the reasons behind their preferences or disinterest in this production.The research was conducted using qualilative methods,seeking information through data and some articles from internal sources.The results show that the majority of informants consider the taste of civet coffe to have unique characteristics,being smoother,not too acidic,and having a distinctive aroma not found in regular coffe.some consumers also interpret,Kopi luwak:Do they really appreciate the unique flavor,or is the purchase decision more influenced by trends,social status,or perceptions of exclusivity? In addition, the lack of adequate information about the production process and the authenticity of the product also becomes on of the barriers in forming a positive perception and consumer loyalty towards kopi luwak.